Bebop to the Boolean boogie an unconventional guide to electronics fundamentals, components, and processes - Maxfield, Clive, 1957- (Amsterdam ; Boston : Newnes, 2003)
From reviews of the first edition: "If you want to be reminded of the joy of electronics, take a look at Clive (Max) Maxfield's book Bebop to the Boolean Boogie."--Computer Design "Lives up to its title as a useful and entertaining technical guide ... well-suited for students, technical writers, technicians, and sales and marketing people."--Electronic Design "Writing a book like this one takes audacity! ... Maxfield writes lucidly on a variety of complex topics without 'writing down' to his audience."--EDN "A highly readable, well-illustrated guided tour through basic electronics."--Science Books & Films "Extremely readable and easy to understand, you'll wonder how people learned about this stuff before this book came along."--New Book Bulletin, Computer Literacy Bookshops * The difference between the analog and digital worlds. * What logic gates are and how to make them from transistors.
Section 1: Fundamental Concepts -- Chapter 1: Analog versus Digital -- Chapter 2: Atoms, Molecules, and Crystals -- Chapter 3: Conductors and Insulators; Voltage, Current, Resistance, Capacitance, and Inductance -- Chapter 4: Semiconductors: Diode and Transistors -- Chapter 5: Primitive Logic Functions -- Chapter 6: Using Transistors to Build Primitive Logic Functions -- Chapter 7: Alternative Numbering Systems -- Chapter 8: Binary Arithmetic -- Chapter 9: Boolean Algebra -- Chapter 10: Karnaugh Maps -- Chapter 11: Using Primitive Logic Functions to Build More Complex Functions -- Chapter 12: State Diagrams, State Tables, State Machines -- Chapter 13: Analog-to-Digital and Digital-to-Analog -- Chapter 14: Integrated Circuits (ICs) -- Chapter 15: Memory ICs -- Chapter 16: Programmable ICs -- Chapter 17: Application-Specific Integrated Circuits (ASICs) -- Chapter 18: Circuit Boards (PWBs and DWBs) -- Chapter 19: Hybrids -- Chapter 20: Multichip Modules (MCMs) -- Chapter 21: Alternative and Future Technologies -- Appendix A: Assertion-Level Logic -- Appendix B: Positive Logic versus Negative Logic -- Appendix C: Reed-Muller Logic -- Appendix D: Gray Codes -- Appendix E: A Reed-Muller Extraction Utility -- Appendix F: Linear Feedback Shift Registers (LFSRs) -- Appendix G: Pass-Transistor Logic -- Appendix H: No-Holds-Barred Seafood Gumbo.
Includes index.
Keywords: Digital electronics -- Popular works; Electronic books; Popular works